Environmental Sustainability and Competitive Advantage in a Wine Tourism Micro-Cluster - Grimstad, S.; Burgess, John (Emerald Group Publishing Limited, 2014)
Purpose – The paper aims to examine the competitive advantage of the environmental behaviour at a firm level and micro-cluster level, building the analysis on Harts model of natural resource-based view of the firm and by using Brown et al.’s framework for analysing contextual resources that would provide locational advantage based on environmental behaviour. The case study examines the drivers and the obstacles to environmental action and demonstrates how clustering has been important in progressing a sustainability agenda. Design/methodology/approach – A case study of a single wine tourism cluster in Australia is undertaken using mixed methods. Findings – The main drivers for environmental action are genuine concerns for the environment by the cluster participants, especially water conservation in the Australian context. Supporting this is the co-ordination of the Lovedale Chamber of Commerce which has promoted its “greening Lovedale” project as a source of regional identity and potential competitive advantage. The obstacles to action are those that are present when small firms dominate, a lack of resources and a lack of know how. Through clustering small businesses can share resources, access specialists and share knowledge.Research limitations/implications – A single cluster case study within the Australian and the wine tourism context confined to one point in time. Practical implications – The clustering of firms in agricultural regions offers the opportunity to achieve individual and collective benefits. Clustering participation can reduce costs, achieve scale economies and share knowledge. These advantages are relevant for environmental actions. In the context of weak or absent government actions and regulations over the environment, regional clusters can utilise the advantages of clustering to meet environmental goals. These in turn can contribute to regional identity and regional comparative advantage. These issues are addressed through the study of the Lovedale wine cluster in Australia. Originality/value – There are few studies of how clustered agricultural industries are addressing environmental challenges independently of central government directives or subsidies. Clustering enables small firms to participate in environmental programs despite being faced by resource and knowledge shortages.